(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Department of Agriculture implements various schemes and programs of the Central and State Governments for the overall welfare of the farming community and ensures timely supply of essential inputs such as seeds, fertilizers, plant protection chemicals, farm implements, micro irrigation units along with effective transfer of technology.Through demonstration to get maximum production from available natural resources like soil, water etc. This improves the economic condition of the farming community and fulfills the food needs of the people. Although the contribution of the agricultural sector to the Gross State Domestic Product is small, agriculture is the largest employment generating activity